Resolution of Defects of Dispute in Indonesian Migrant Worker Placement Agreements (Study at BP3MI Jakarta) - Negara, Revolusi Shandi; Ramadhani, Dwi Aryanti (Journal of Law, Politic and Humanities, 2024)
This research discusses the resolution of non-performance disputes in agreements to place Indonesian migrant workers at BP3MI Jakarta, especially the cases of PMI Watini and PT. Main Independent Success. Through normative juridical research and qualitative analysis, BP3MI Jakarta is proven to have an important role in handling disputes and providing legal protection for Indonesian migrant workers. The results show that mediation was successful in resolving the PMI Watini dispute with a refund of fees and a certificate of debt repayment. This research also links the findings with previous research, and suggests evaluating the effectiveness of BP3MI dispute resolution in various regions, analyzing PMI protection policies, international comparative studies, research on the role of stakeholders, other cases of default, developing a monitoring system, and evaluating social and economic impacts.